Refrigeration through voltage-controlled entropy change - Binek Christian (2017)
A method for refrigeration through voltage-controlled entropy change includes applying a voltage signal to a piezoelectric material to generate strain in the piezoelectric material, generating strain in a magnetic material attached to the piezoelectric material, and generating a change in a temperature of the magnetic material in response to the strain in the magnetic material.